2021
DOI: 10.1016/j.joto.2021.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal colonization of otopathogens in South Indian children with acute otitis media – A case control pilot study

Abstract: Background Acute otitis media (AOM) is an inflammatory disease of the middle ear causing significant morbidity in early childhood. A pilot study was undertaken to identify the role of various risk factors South Indian children with AOM, especially the role of nasopharyngeal otopathogens. Methodology A prospective case control pilot study was conducted in children aged below six years, presenting to a single tertiary care from 2018 to 2019. Fifty cases with AOM and 45 ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…There are limitations in the study. Recently, Moraxella catarrhalis has been detected in 6%-20% of AOM cases, 1,3,4 but many multiplex PCR platforms do not include M. catarrhalis in their respiratory tract panels. Thus, a proportion of viral-classified AOM may be M. catarrhalisrelated.…”
Section: Fu N D I N G I N Fo R M Ati O Nmentioning
confidence: 99%
See 2 more Smart Citations
“…There are limitations in the study. Recently, Moraxella catarrhalis has been detected in 6%-20% of AOM cases, 1,3,4 but many multiplex PCR platforms do not include M. catarrhalis in their respiratory tract panels. Thus, a proportion of viral-classified AOM may be M. catarrhalisrelated.…”
Section: Fu N D I N G I N Fo R M Ati O Nmentioning
confidence: 99%
“…The development of acute otitis media (AOM) is strongly associated with viral respiratory tract infection followed by a bacterial infection rising from the nasopharynx to the middle ear. There is limited evidence on the association of nasopharyngeal viral and bacterial multiplex polymerase chain reaction (PCR) findings with AOM in clinical practice in acutely ill children 1–4 . We aimed to evaluate the occurrence of AOM according to different nasopharyngeal viral and bacterial detections in real‐life setting using commercial multiplex PCR.…”
Section: Respiratory Viruses Proportion Of Children With Aom Crp In C...mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, serotypes 3, 6A, 6B, 9V, 14, 19A, 19F and 23F are the most common pneumococcal serotypes that cause AOM worldwide [ 10 ]. However, non-vaccine serotypes, such as 11A and 15B/15C, are also known to frequently cause AOM worldwide [ 15 ]. Recently, it was reported that non-PCV13 serotypes (23A and 15B/C) were common in children under 5 years old with otitis media and those without in Taiwan [ 16 ].…”
Section: Introductionmentioning
confidence: 99%